Designing, Conducting, and Analyzing Empirical Studies - Kraemer, Eileen (Electronic Communications of the EASST, 2008)
LED08 is concerned with the role of diagrams in communication between engineers. Evaluation is at the heart of an engineering approach to designing and/or selecting diagrams that are well-suited to a particular task. In this talk I will survey several methods for conducting empirical studies of such diagrams, discuss approaches to analysis, review several studies that we have conducted, and summarize the lessons learned in the process.